2010
DOI: 10.1248/cpb.58.769
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Dissolution of Naproxen and Flurbiprofen from a Novel Ternary .GAMMA.-Cyclodextrin Complex

Abstract: A crystalline ternary complex was prepared by sealed-heating of naproxen (NPX) with a flurbiprofen (FBP)/g g-cyclodextrin (g g-CD) inclusion complex. The dissolution rates of NPX and FBP in the ternary complex were almost the same, indicating that FBP and NPX from the complex dissolved simultaneously. The ternary CD complex showing a fascinating dissolution property could be a new formulation for combination therapies.Key words cyclodextrin; dissolution; powder X-ray diffraction; sealedheating; inclusion compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…The recent study of an interaction of CD and drug in the solid state found a novel complex. Other drugs existed in the intermolecular space among the regularly threedimensional structures gathering columnar type structures that were assembled from CD alone or an inclusion complex between CD and drug (68)(69)(70). It suggests that CD10 and CD14 can form not only inclusion complexes, but also noninclusion complexes in solid state, since they can form a similar structure with the continuous cavity in the crystal state as shown in Fig.…”
Section: Application Of Lr-cdsmentioning
confidence: 96%
“…The recent study of an interaction of CD and drug in the solid state found a novel complex. Other drugs existed in the intermolecular space among the regularly threedimensional structures gathering columnar type structures that were assembled from CD alone or an inclusion complex between CD and drug (68)(69)(70). It suggests that CD10 and CD14 can form not only inclusion complexes, but also noninclusion complexes in solid state, since they can form a similar structure with the continuous cavity in the crystal state as shown in Fig.…”
Section: Application Of Lr-cdsmentioning
confidence: 96%
“…In fact, it has already been found that the NPX (FBP/g-CD) ternary complex showed specific dissolution characteristics in which two species of APIs were released simultaneously after being dispersed into a dissolution media. 17 We have been investigating this unique dissolution from the ternary complex. Understanding the structures and molecular state of the ternary complexes described here could help to explain the dissolution mechanism.…”
Section: Ternary Complex Formation Using Other Guest Drugsmentioning
confidence: 99%
“…16 A previous study showed that the sealed-heating technique induced the formation of a crystalline ternary g-CD complex containing two pharmaceutical drugs, naproxen (NPX) and flurbiprofen (FBP). 17 The ternary complex exhibited a unique dissolution behavior-NPX and FBP dissolved simultaneously. It has been speculated that, in the complex, FBP was incorporated into the cavity of g-CD and NPX was located in the intermolecular spaces in the g-CD columns.…”
Section: Introductionmentioning
confidence: 99%
“…A observação de funcionalidades supramoleculares e características conformacionais dos componentes do cristal é uma etapa decisiva durante a seleção de agentes de co-cristalização e formadores de sais com maior probabilidade de formar modifi cações cristalinas sob condições laboratoriais. Esta prática também permite predizer a compatibilidade de cocristalização de diferentes fármacos dentro de uma fase cristalina 32 , o que, em determinados casos, é desejado do ponto de vista farmacotécnico dado que a incorporação de múltiplos fármacos dentro de uma única fase sólida pode evitar incompatibilidades físicas entre diferentes insumos farmacêuticos 33 , sendo isto, entretanto, algo pouco reportado na literatura 34 .…”
Section: Estratégias De Síntese De Novas Formas Cristalinas De Fármacosunclassified